Sub-conjunctival dislocation of posterior chamber intra-ocular lens: five years after manual, small-incision cataract surgery - Joshi, Rajesh Subhash (Nepalese Journal of Ophthalmology, 2014)
Introduction: Ocular trauma can cause serious complications in eyes operated for cataract. Case: A 70-year- old lady had sustained blunt trauma to the left lower lid which resulted in a sub-conjunctival dislocation of the posterior chamber intraocular lens (PCIOL). The patient had undergone an uneventful manual, small-incision, sutureless cataract surgery with implantation of a PCIOL for senile cataract five years ago in the same eye. She had no ocular or systemic predisposing factors for wound dehiscence. Surgical exploration revealed a scleral rupture 7 mm in length, 2 mm behind the limbus at the 12’O clock position along the surgically-constructed wound. However, the scleral tunnel was not damaged. The PCIOL was removed. Wound closure was done to avoid infection of the intraocular structures. Her best-corrected visual acuity was 20/60 at the three months’ follow-up. Conclusion: Surgeons should be aware of such complications occurring due to trauma. We recommend suturing of the scleral wound to strengthen it in cases of a deep scleral groove or when there is a possibility of a premature entry of the wound into the anterior chamber. DOI: http://dx.doi.org/10.3126/nepjoph.v6i1.10777   Nepal J Ophthalmol 2014; 6 (2): 91-94